Capacitance behavior of ordered mesoporous carbon/Fe2O3 composites: Comparison between 1D cylindrical, 2D hexagonal, and 3D bicontinuous mesostructures. (November 2015) - Hu, Junkai; Noked, Malachi; Gillette, Eleanor; Gui, Zhe; Lee, Sang Bok
Abstract: The combination of high electronic conductivity, enhanced ionic mobility, and high pore volume make ordered mesoporous carbons promising scaffolds for active energy storage materials. However, mesoporous morphology and structural stability needs to be more thoroughly addressed. In this paper, we demonstrate Fe2 O3 impregnation into 1D cylindrical (FDU-15), 2D hexagonal (CMK-3), and 3D bicontinuous (CMK-8) symmetries of mesoporous carbons. We use these materials for a systematic study of the effect of mesoporous architecture on the structure stability, ion mobility, and performance of mesoporous composite electrodes. By optimization of the porous structure, the oxide impregnation enabled relatively high performance: >650 F g −1 of Fe2 O3 and >200 F g −1 total capacitance. This work highlights the new considerations of structure degradation in different pore symmetries with active material impregnation and its effect on ion mobility and electrochemical performance in porous scaffold electrodes. The results show that the most commonly used 2D CMK-3 is not suitable as a host material due to its poor structure stability and ion mobility, while the 1D FDU-15 and 3D CMK-8 have their own merits related to framework stability and porous structures.